Global, regional, and national burdens of traumatic brain injury, spinal cord injury, and skull fracture and their attributable risk factors from 1990 to 2021: a systematic analysis of the global burden of disease study 2021 - Yikang Wang (Frontiers in Public Health)
BackgroundTraumatic central nervous system (CNS) injuries—particularly traumatic brain injury (TBI), spinal cord injury (SCI), and skull fractures—represent a significant global health challenge. Previous estimates have lacked a comprehensive global analysis of these injuries and their associated risk factors. Herein, we aimed to examine the epidemiological patterns, temporal trends and risk factors of TBI, SCI, and skull fractures globally from 1990 to 2021.MethodsWe extracted data from the Global Burden of Disease Study (GBD) 2021, including the prevalence, incidence, and years lived with disability (YLDs) of TBI, SCI, and skull fractures across 204 countries and territories from 1990 to 2021. Data were presented as both numerical counts and age-standardized rates (ASRs) per 100,000 population, with corresponding uncertainty intervals. To assess temporal trends in disease burden, we calculated the estimated annual percentage change (EAPC) with associated 95% confidence intervals.ResultsCompared with 1990, the number of global incident cases in 2019 changed by 122.56, 121.29, and 97.49% for TBI, SCI, and skull fracture, respectively. During the 30-year study period, there was a downward trend in the ASR of prevalence, incidence and YLDs for TBI (EAPC = −0.68, −0.8 and −0.66, respectively), SCI (EAPC = −0.73, −0.81 and −1.01, respectively) and skull fracture (EAPC = −1.37, −1.15 and −1.38, respectively). Regions with higher sociodemographic indices had higher incidences, incidence rates, and YLDs for all three types of CNS injury. The burden of CNS injury varies notably among regions and nations. Eastern Europe, Central Europe, southern Latin America, Australasia, and high-income North America were the GBD regions with the highest burden of CNS injury, and the burdens of TBI, SCI, and skull fracture showed the most significant increasing trends in the Caribbean. Young-to-middle-aged men (15–39 years) bore the primary burden of TBI, SCI, and skull fractures. Falls were the leading specific risk factor for all three types of CNS injury, followed by motor vehicle road injuries. The global burden of TBI, SCI, and skull fractures is projected to decline through 2040, both in terms of absolute case counts and age-standardized incidence rates.ConclusionThe global, regional, and national burdens of TBI, SCI, and skull fractures—reflected by their prevalence, incidence, and YLDs—exhibit significant disparities. Our findings can inform policymakers in formulating future strategies for managing traumatic CNS injuries, with priority given to targeted preventive measures against risk factors to mitigate the burden of these life-threatening and disabling CNS conditions.